Interconexión a nivel ciclónico-atmosférico entre el Caribe y el Pacífico centroamericano - Banichevich, Antonio; Lizano, Omar G. (Revista de Biología Tropical, 1998)
Some atmospheric properties in the Pacific and Caribbean marine basins close to the Central American Isthmus and their possible interconnections are analized, based on a statistical study. The band describing southern Nicaragua is taken as reference, because it has the least orographic features that may disturbe the Trade winds flowing from the northwest (NW) and from the southeast (SE). The atmospheric properties are associated to the incidence of synoptic phenomena like tropical cyclones and their probability of crossing the Isthmus with minimun energy loss. The warm El Niño-Southern Oscillation (ENSO) eventsproctuced a systematic weakening of sporadic cyclone type events in the western Atlantic, while in the eastern Pacific, because of surface water temperatures higher than 27°C, they are reinforced. During the transition from warm-ENSO to cold-ENSO events, there are interconnections between both oceanic basin with cyclonic systems crossing the Isthmus, mainly across the Nicaragua depression (from the Atlantic to the Pacific); and with only one Case, through Tehuantepec (from the pacific to the Atlantic). During the cold-ENSO events, similar.conditions to the transition stage can be expected; i.e., the number of events increased in the Atlantic Basin while in the Pacific they are reduced.